Biochemical diversity of bacterial isolates from paddy soils of peninsular Malaysia - Mohd Yusof, Mazlin; Mohd Saud, Halimi; Tan, My Pein (Universiti Putra Malaysia Press, 2009)
In this study, the diversity of bacterial isolates from paddy soil located in several rice growing areas of Peninsular Malaysia was evaluated. Phenotypic and physiological characteristics of the isolates were recorded to categorize and identify the bacteria. Ten strains of bacteria were recovered from six different locations (Alor Bakat, Kg. Seligi, Bachok, Kelantan; Sekinchan, Selangor; Kobah, Kedah; and Sg. Batu Pahat, Perlis). The spread-plate technique on nutrient agar at pH 7.0 was used to isolate and purify all the strains. The characteristic of the bacteria strains were determined using the Gram staining, motility test, as well as the shape and size of the single colony on solid media. From the various tests conducted, nine isolates were identified as Gram-positive rods, and only one was Gram-negative cocci. Further biochemical tests were carried out to determine the ability of these bacteria strains to hydrolyze starch, casein and gelatine, ferment carbohydrate (glucose, lactose and sucrose), enzyme production (catalase and oxidase), MR-VP tests and growth under anaerobic condition; the elevated NaCl was also examined. On the basis of these tests and the biochemical characteristics, nine of the strains belonged to the same genus, Bacillus, with three potentially different species. Meanwhile, only one strain showed the characteristics related to Proteus mirabilis. This study also showed that the dominant bacteria genera are generally limited, despite the contrasting geographical location and soil characteristics in which the strains were isolated.